The Effect of Thermal Perturbation on a Polymer Material’s Tensile Test via Simulation and Experimental Analysis - Sazali, M.Q.; Suffian, M.S.Z.M.; Khan, A. A.; Yassin, A.; Mohamaddan, Shahrol; Yusof, M.; Rashidi, S.A.; Saad, M.H.I. (UTEM, 2017)
Polymers are made from pieces of monomer that can be connected into a long chain. Natural rubber is studied in this research. In this research, tensile testing was conducted to the rubber specimen in order to check the heat release from the specimen. A thermocouple device was used to measure the specimen's temperature during tensile testing. The data from the tensile test were used to generate the stress vs strain curve. Computer simulation study was also performed. The results show that the temperature reading from the thermocouple device has increased to prove that there was a heat release from the tensile test. The heat was detected after the specimen’s fracture. The simulation test proved the same phenomena as the experimental test.